Geografia, lugar e lugares: o caso do Parque da Redenção em Porto Alegre - RS - Herrmann, Gustavo (2018)
The research presents a geographic cut of the Farroupilha Park (popularly known as Redenção) located in Porto Alegre/RS. Nowadays the Park adds a diversity of leisure areas and also has in its internal transit a wide circulation of the public in its spaces, a cultural diversity of social groups, that may or may not interact with each other when they make use of collective spaces. Given the dynamism that presents the space of the park, we ask: what are the possibilities of Geography to understand the affective relations of social subjects with certain places? In particular, what are the relevant aspects that emerge as affective relationships of the public with the "place" Farroupilha Park (Redemption)? Moreover, what are the methodological potentialities that Geography offers us to analyze these affective relations with this place? The role of a large park in a cosmopolitan city and its importance for the people living in this city are the areas of leisure and spaces that favor socialization, exchange of information, and experiences among the people who go there. It is a break from the routinely grayness of the city in contrast with the green of nature, taking back intrinsic aspects of human nature from the need to be in touch with the environment. Thus, the whole relation that the subject creates with the space that he/she goes to produces a positive affective bond (topfilia) or negative (topphobia) and from this presupposition, the main objective of the project takes its form to understand the relationship that the subjects create with the Redenção (popular name given to the Farroupilha Park). The work will use mental maps as an instrument of analysis. These provide the ability to graphically represent the places where people go. In this case, the Farroupilha park. We call "places of sociability" the places in which interaction between people who are in the park occur, resorting to the concept of sociability. They are mental representations of places that people bring into their memory through different moments and life experiences in space. It is around these experiences in this place of people who attend the Redemption that we search through mental maps to understand the affective relationship that park goers may or may not develop with the place/space park Farroupilha. Geography with its vast scope of study in various fields of knowledge, still ceases to forget to make the relation of being to space, which led to the construction of this project. That, in the context of Geographical research, brings a contribution of study that focuses on the humanistic relations of social subjects with space. Aiming to focus on cultural and subjective aspects that make up the "being" spatial.The research presents a geographic cut of the Farroupilha Park (popularly known as Redenção) located in Porto Alegre/RS. Nowadays the Park adds a diversity of leisure areas and also has in its internal transit a wide circulation of the public in its spaces, a cultural diversity of social groups, that may or may not interact with each other when they make use of collective spaces. Given the dynamism that presents the space of the park, we ask: what are the possibilities of Geography to understand the affective relations of social subjects with certain places? In particular, what are the relevant aspects that emerge as affective relationships of the public with the "place" Farroupilha Park (Redemption)? Moreover, what are the methodological potentialities that Geography offers us to analyze these affective relations with this place? The role of a large park in a cosmopolitan city and its importance for the people living in this city are the areas of leisure and spaces that favor socialization, exchange of information, and experiences among the people who go there. It is a break from the routinely grayness of the city in contrast with the green of nature, taking back intrinsic aspects of human nature from the need to be in touch with the environment. Thus, the whole relation that the subject creates with the space that he/she goes to produces a positive affective bond (topfilia) or negative (topphobia) and from this presupposition, the main objective of the project takes its form to understand the relationship that the subjects create with the Redenção (popular name given to the Farroupilha Park). The work will use mental maps as an instrument of analysis. These provide the ability to graphically represent the places where people go. In this case, the Farroupilha park. We call "places of sociability" the places in which interaction between people who are in the park occur, resorting to the concept of sociability. They are mental representations of places that people bring into their memory through different moments and life experiences in space. It is around these experiences in this place of people who attend the Redemption that we search through mental maps to understand the affective relationship that park goers may or may not develop with the place/space park Farroupilha. Geography with its vast scope of study in various fields of knowledge, still ceases to forget to make the relation of being to space, which led to the construction of this project. That, in the context of Geographical research, brings a contribution of study that focuses on the humanistic relations of social subjects with space. Aiming to focus on cultural and subjective aspects that make up the "being" spatial.